Effect of breath holding at the end of the inspiration and expiration phases on liver stiffness measured by 2D-MR elastography. - Ren, Hao; Yang, Dawei; Xu, Hui; Pang, Kai; Shi, Yiwen; Guan, Qiushuang; Yang, Zhenghan (Abdominal Radiology, 2021)
Purpose: Evaluate the effect of breath holding at the end of the inspiration and expiration phases on the measurement of liver stiffness by 2D-MR elastography (MRE). Methods: The study included 61 subjects, of which 31 subjects were pathologically confirmed liver fibrosis patients [liver fibrosis group (LFG)] and 30 healthy subjects [healthy group (HG)]. MRE was used to measure the liver stiffness of subjects in inspiration breath-hold (IBH) and expiration breath-hold (EBH) states. Results: In IBH and EBH states, the liver stiffness measured by MRE was not significantly different in the HG (P = 0.125, > 0.05), while the LFG showed a significant difference (P <0.001). Also, a significant difference was observed between the change values in the mild/moderate fibrosis group (MFG) and advanced fibrosis group (AFG) (P = 0.005, < 0.05). Conclusions: The liver stiffness values in patients with liver fibrosis were affected by breath-holding states. The higher the stage of liver fibrosis, the greater the change in liver stiffness values, but no significant difference was observed between liver stiffness values in healthy subjects under the two breath-holding conditions. Different breath-holding states are factors influencing liver fibrosis stiffness measured by MRE, which should be given due attention in both clinical and research contexts.